O Serviço de Assistência Jurídica como uma estratégia de ensino-aprendizagem no curso de Direito: a expectativa dos estudantes da Universidade Estadual de Feira de Santana-BA - Grimaldi, Bruna Neves Rabelo Gonzalez (2022)
The National Curriculum Guidelines for the Undergraduate Course in Law, regulated by Resolution CNE/CES nº5, of December 17, 2018, establish for Higher Education Institutions that offer the respective course, the mandatory existence of a Nucleus of Legal Practices (NPJ, in Portuguese) with the purpose of coordinating the curricular actions of Legal Practice through professional training activities and legal assistance services under its responsibility. Therefore, Legal Practice is a mandatory curricular component for the creation and recognition of legal courses in Brazil. At the Feira de Santana State University – (UEFS, in Portuguese), the Legal Practice Nucleus houses the set of activities that make up the Legal Practice of the Law Course: practice laboratories, external earnings and the Legal Assistance Service (SAJ-UEFS, in Portuguese), which constitutes the investigation space of this research. Its characteristics and especially the learning expectations that students of the Bachelor of Laws at UEFS have about their role in the professional training process itself is the central theme of the present study. Based on a theoretical survey on the subject, involving the historical and normative process of legal courses in Brazil, the learning process in higher education, with emphasis on the significant learning proposal of David Ausubel (2003) and the Pedagogical Project of the Course of Law of the institution chosen for the study, to define itself, to carry out field research through an empirical research with a qualitative, exploratory and descriptive methodological approach, which used a written instrument as a data collection instrument, applied through the Google platform Form, composed of open and closed questions aimed at students from the 7th to the 10th semester of the UEFS Law course, since this dissertation was developed within the pandemic period established by Covid-19 (2020-2022). The data were analyzed based on the proposal of content analysis formulated by Bardin (2011), specifically by the description, categorization and interpretation of the data produced with the students. Among the findings, it is important to highlight the need to review the pedagogical projects of the Law course about the role of the NPJ and the SAJ itself for the training process, to break the conservative paradigm of learning and get closer, both to the training needs of students, as well as of the community it serves with the provision of services. Another fundamental aspect refers to the need to articulate the SAJ with teaching, research, and university extension, thus promoting a more meaningful learning process consistent with its conception.